2007
DOI: 10.1182/blood-2006-07-035576
|View full text |Cite
|
Sign up to set email alerts
|

A newly established murine immature dendritic cell line can be differentiated into a mature state, but exerts tolerogenic function upon maturation in the presence of glucocorticoid

Abstract: IntroductionImmature dendritic cells (DCs), specialized in the uptake of antigen, 1 reside as sentinels in almost every tissue. Under steadystate conditions, a small fraction of DCs acquire a semimature state and migrate to the draining secondary lymphoid organs. There, these semimature DCs exert tolerogenic functions by inducing apoptosis, anergy, or even a regulatory state in interacting autoreactive T cells that escaped elimination during negative thymic selection. In addition to natural regulatory T cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 63 publications
(49 reference statements)
1
36
0
Order By: Relevance
“…MPI cells are model cells of differentiated tissue macrophages prepared without genetic manipulation or oncogenic transformation and share a number of properties with alveolar macrophages. Using GM-CSF and M-CSF, DC lines have been established previously from mouse spleen (23,24). We compared one of them, the SP37A3 cells (24), to the MPI cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MPI cells are model cells of differentiated tissue macrophages prepared without genetic manipulation or oncogenic transformation and share a number of properties with alveolar macrophages. Using GM-CSF and M-CSF, DC lines have been established previously from mouse spleen (23,24). We compared one of them, the SP37A3 cells (24), to the MPI cells.…”
Section: Discussionmentioning
confidence: 99%
“…Using GM-CSF and M-CSF, DC lines have been established previously from mouse spleen (23,24). We compared one of them, the SP37A3 cells (24), to the MPI cells. Our analysis of the gene expression profiles, surface markers, and responses to innate stimuli showed that SP37A3 cells are quite different from MPI cells.…”
Section: Discussionmentioning
confidence: 99%
“…11,12,15 Consequently, glucocorticoids impair T-cell stimulatory capacity of DCs. 13,14,16,17 In addition, glucocorticoids may reduce the number of DCs via inhibiting DC migration and increasing DC apoptosis, 7,9,10,12,15,[18][19][20][21][22][23][24][25] although some other reports suggest that glucocorticoids do not induce DCs apoptosis. 13,16,26,27 It is not known whether different DC subsets have differential sensitivity to glucocorticoid-induced apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Bone marrow-derived DCs (BMDCs) were generated according to a previously published protocol [16]. Bone marrow cells were grown in culture medium (IMDM, 10% FCS, 50 µ M β-mercaptoethanol, 2 m M glutamine, 100 µg/ml streptomycin, 100 U/ml penicillin supplemented with 5% of granulocyte-monocyte colony-stimulating factor (GM-CSF)-containing cell culture supernatant derived from X63.Ag8–653 myeloma cells stably transfected with a murine GM-CSF expression construct, a kind gift from Dr. B. Stockinger, National Institute for Medical Research, London, UK).…”
Section: Methodsmentioning
confidence: 99%